2019
DOI: 10.1101/777870
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low E2F2 activity is associated with high genomic instability and PARPi resistance

Abstract: 34The E2F family, classically known for a central role in cell cycle, has a number of emerging roles 35 in cancer including angiogenesis, metabolic reprogramming, metastasis and DNA repair. E2F1 36 specifically has been shown to be a critical mediator of DNA repair; however, little is known about 37 DNA repair and other E2F family members. Here we present an integrative bioinformatic and 38 high throughput drug screening study to define the role of E2F2 in maintaining genomic integrity 39 in breast cancer. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…A previous study has reported that E2F2 transcriptionally accumulates in response to DNA damage, promotes Rad51 foci formation and maintains the genomic stability and integrity in neuronal cells [51]. More recently, it was reported that low E2F2 activity is correlated with high genomic instability and poor response to PARPi [52]. Notebally, it has been poorly described for the role of E2F2 in gene instability and repair in the context of cancer until now.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has reported that E2F2 transcriptionally accumulates in response to DNA damage, promotes Rad51 foci formation and maintains the genomic stability and integrity in neuronal cells [51]. More recently, it was reported that low E2F2 activity is correlated with high genomic instability and poor response to PARPi [52]. Notebally, it has been poorly described for the role of E2F2 in gene instability and repair in the context of cancer until now.…”
Section: Discussionmentioning
confidence: 99%